ANALISIS KUALITAS SPERMA HEWAN UJI: METODE PENGHITUNGAN BILANGAN SPERMA EPIDIDIMIS TIKUS - Muhammad Ja’far Luthfi (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
Sperm sample from epididimal source can be determined its sperm number using minimal amount of equipment. These method will aid researcher and practitioner in sperm number analysis in the field of male animal reproduction accurately.